APPLICATION OF THE DESIGN THINKING METHOD TO DETERMINING MARKETING STRATEGY IN TEEFEES COLLECTIONS - Wendia Putra Paputungan; Jurry Hatammimi; Arien Arianti Gunawan (SEAN Institute, 2023)
This research was conducted in response to the rapid growth of the fashion industry subsector, intense business competition, and the impact of the COVID-19 pandemic on businesses in the fashion industry. Teefees Collection is one of the fashion businesses in Manado, focusing on selling fashion products. They sell not only clothing products but also other accessory products. However, the Teefees Collection faced challenges such as declining sales, lack of engagement on social media, unattractive packaging design, and suboptimal marketing division performance. Design thinking was used as the method of approach in this research, consisting of five stages: empathize, define, ideate, prototype, and test. The goal of this research was to formulate marketing strategies using the design thinking method to increase sales for the Teefees Collection. This research used qualitative methods for data collection by interviewing both internal and external stakeholders of Teefees Collection. The findings provided recommendations regarding new packaging designs, promotional strategies such as Upload and Get Discount (UGD), e-card membership, mixed bundling, and discounts on special days. Moreover, this research also provided content planning for Instagram. It is also recommended for Teefees Collection's marketing division to take marketing training.